2020
DOI: 10.1111/dom.14201
|View full text |Cite
|
Sign up to set email alerts
|

Association between visit‐to‐visit HbA1c variability and the risk of cardiovascular disease in patients with type 2 diabetes

Abstract: Aim To investigate the association between visit‐to‐visit HbA1c variability and the risk of cardiovascular disease in patients with type 2 diabetes. Materials and methods We performed a retrospective cohort study of 29 260 patients with at least four HbA1c measurements obtained within 2 years of their first diagnosis of type 2 diabetes. Different HbA1c variability markers were calculated, including the standard deviation (SD), coefficient of variation (CV) and adjusted SD. Cox proportional hazards regression m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
38
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(40 citation statements)
references
References 29 publications
2
38
0
Order By: Relevance
“…Previous papers on “variability” have used various indices to evaluate their variability. SD has been used to evaluate the glycemic, blood pressure, and fasting TG variability ( 19 , 20 , 32 , 33 ) ( 34 , 35 ); the Adj-SD has also been used to evaluate the glycemic and fasting TG variability with adjusting for the number of measurements ( 19 , 21 , 22 , 36 ); and the MMD has been used to evaluate the glycemic and blood pressure variability ( 23 , 24 , 37 , 38 ). Our study suggested that the SD and Adj-SD might be more reliable than MMD, but MMD is calculated more easily than the other two.…”
Section: Discussionmentioning
confidence: 99%
“…Previous papers on “variability” have used various indices to evaluate their variability. SD has been used to evaluate the glycemic, blood pressure, and fasting TG variability ( 19 , 20 , 32 , 33 ) ( 34 , 35 ); the Adj-SD has also been used to evaluate the glycemic and fasting TG variability with adjusting for the number of measurements ( 19 , 21 , 22 , 36 ); and the MMD has been used to evaluate the glycemic and blood pressure variability ( 23 , 24 , 37 , 38 ). Our study suggested that the SD and Adj-SD might be more reliable than MMD, but MMD is calculated more easily than the other two.…”
Section: Discussionmentioning
confidence: 99%
“…Blood glycated hemoglobin (HbA 1c ), reflecting blood glucose control during a time span of one to two months, was measured using standardized assays in a central laboratory (Medix Laboratories, Espoo Finland) [12]. Three or more HbA 1c values over the course of ten years before the visit (median count 16, IQR [10][11][12][13][14][15][16][17][18][19][20][21][22][23] were obtained in order to calculate overall mean HbA 1c (HbA 1c -mean overall ) for each individual to better delineate long-term glucose control. These values were collected from local laboratories using standardized methods (HPLC) with a normal range of 4-6%.…”
Section: Measures Of Blood Glucose Controlmentioning
confidence: 99%
“…Although no consensus has been reached regarding the standard definition or measuring methods for glycemic variability, coefficient of variation (CV) or standard deviation (SD) of visit-to-visit fasting plasma glucose (FPG) or HbA1c have been mostly applied for measuring of long-term glycemic variability in previous studies [ 13 , 14 ]. Interestingly, previous studies evaluating the association between glycemic variability and stroke in people with diabetes showed inconsistent results [ 15 21 ]. Some studies showed that higher glycemic variability may be associated with higher risk of stroke [ 15 , 17 , 19 , 21 ], while other studies did not [ 16 , 18 , 20 ].…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, previous studies evaluating the association between glycemic variability and stroke in people with diabetes showed inconsistent results [ 15 21 ]. Some studies showed that higher glycemic variability may be associated with higher risk of stroke [ 15 , 17 , 19 , 21 ], while other studies did not [ 16 , 18 , 20 ]. Moreover, different parameters for long-term glycemic variability were applied among these studies, three with FPG-CV [ 15 , 17 , 19 ], two with FPG-SD [ 17 , 19 ], four with HbA1c-CV [ 18 21 ], and the other four with [ 16 , 18 , 19 , 21 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation